O lugar da metafísica na filosofia da religião de Bernard Lonergan / The place of metaphysics in Bernard Lonergan’s philosophy of religion - de Oliveira, Ednilson Turozi (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->Esse artigo reflete sobre o reposicionamento da metafísica na filosofia da religião de Lonergan. Para Lonergan, a metafísica não mais ocupa o primeiro lugar, e sim um lugar terciário. A implicação para a filosofia da religião é a de que,nela,a teoria cognitiva, a história, a hermenêutica, e a metodologia são priorizadas. Abstract This article reflects upon the repositioning of metaphysics in Lonergan´s Philosophy of Religion. For Lonergan, instead of occupying the first place, metaphysics is now in a tertiary position. The implication of such relocation for the philosophy of religion is that, with it, cognitional theory, history, hermeneutics, and methodology become prioritized.